Functional outcomes of endoscopic arytenoid abduction lateropexy for unilateral vocal cord paralysis with dyspnea - Matievics Vera (EUROPEAN ARCHIVES OF OTO-RHINO-LARYNGOLOGY, 2017)
In unilateral vocal cord paralysis (UVCP), hoarseness is usually the leading symptom; however, the diminished airway might lead to breathing problems as well, especially with exertion. The application of the classic resection glottis enlarging or medialization procedures might shift the breathing and/or the voice to a worse condition. The non-destructive endoscopic arytenoid abduction lateropexy (EAAL) might be a solution for this problem. The aim of our study was to analyze the phonatory and respiratory outcomes of this treatment concept. The first year phoniatric [Jitter, Shimmer, harmonics-to-noise ratio (HNR), maximum phonation time (MPT), fundamental frequency (F 0), Voice Handicap Index (VHI), Dysphonia Severity Index (DSI), Global-Roughness-Breathiness scale (GRB)], peak inspiratory flow (PIF), and quality of life (QoL) were evaluated in ten UVCP patients treated by EAAL for dyspnea generally presented on exertion. PIF, Jitter, QoL, GRB, and VHI significantly improved. DSI, HNR, and MPT got non-significantly better. F 0 slightly increased in all patients, a mild deterioration of shimmer was observed. These results prove that improving respiratory function is not necessarily associated with a deterioration in voice quality. The EAAL provides a significant improvement in breathing and the vibratory parameters of the postoperative, more tensed and straightened vocal cords proved to be more advantageous than the original (para) median 'loose' position. The over-adduction of the contralateral side more or less compensates for the disadvantageous, more lateral position of the operated side. EAAL might be an alternative treatment for unilateral vocal cord paralysis associated with breathing problems.